Vampires, bones and treacle scones - Dunnett, Kaitlyn (Dunnett, Kaitlyn. Liss MacCrimmon mystery., 2013)
Halloween is approaching and newlywed Liss MacCrimmon Ruskin is tapped by the Moosetookalook Small Business Association to organize a community fundraiser. Liss throws herself into plans to turn an abandoned mansion into a "haunted house." And then, to Liss' horror, the fake skeleton she's acquired for a special effect is replaced with a real body -- and it's someone she knows.